New oxidizing reagents based on iodobenzenesulfonic acid; Dombay Organic Conference Cluster, DOCC-2016 - Mironova I. A. Irina Andreevna; Yusubova R. Ya. Roza Yavidovna; Zhdankin V. V. Viktor Vladimirovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2016, 2016)
Title screen